State Responsibility in Protecting Citizens’ Digital Rights under Indonesian Constitutional Law - Bayu Romadon; Ihsan Ihsan; Muslim Muslim (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This study examines the constitutional construction of state responsibility in protecting citizens digital rights under Indonesian constitutional law within the context of expanding digital governance and increasing risks of surveillance based state intervention. The research employs non empirical normative legal research grounded in doctrinal, statutory, conceptual, and constitutional approaches through analysis of the Constitution of the Republic of Indonesia of 1945, the Electronic Information and Transactions Law, the Personal Data Protection Law, the Human Rights Law, Constitutional Court decisions, and relevant digital constitutionalism scholarship. The findings demonstrate that constitutional guarantees concerning privacy, freedom of expression, and informational autonomy have not yet been translated into coherent operational legal mechanisms capable of limiting excessive digital surveillance and protecting online civil liberties. Indonesian digital governance continues to reflect fragmented regulatory structures, weak institutional accountability, and insufficient constitutional safeguards concerning algorithmic governance and state monitoring practices. The study proposes a reconstruction of constitutional state obligations based on proportionality, democratic constitutionalism, judicial accountability, and algorithmic due process in order to establish enforceable constitutional protections capable of preserving civil liberties and democratic participation within technologically mediated governance systems.